2020
DOI: 10.3390/jcm9072232
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Post-Stroke: Short- and Long-Term Effect on Depression, Anxiety, Apathy and Aggression (Research Study—Part of PROPOLIS Study)

Abstract: Background: Stroke patients are particularly vulnerable to delirium episodes, but very little is known about its subsequent adverse mental health outcomes. The author’s objective was to explore the association between in-hospital delirium and depression, anxiety, anger and apathy after stroke. Methods: A total of 750 consecutive patients with acute stroke or transient ischemic attack, were screened for delirium during hospitalization. Patients underwent mental health evaluation in hospital, 3 and 12 months pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…This would imply that the anxiety levels in patients with delirium are of clinical importance at 18 and 36 months (Mean ( SD ): 5.6 (1.2) and 6.2 (1.3) respectively). Though Kowalska et al [ 54 ] recently found delirium to be a risk factor for anxiety 3 months after stroke, our findings suggest that the subsequent anxiety symptoms can be present or even increase over a longer timeframe.…”
Section: Discussioncontrasting
confidence: 80%
“…This would imply that the anxiety levels in patients with delirium are of clinical importance at 18 and 36 months (Mean ( SD ): 5.6 (1.2) and 6.2 (1.3) respectively). Though Kowalska et al [ 54 ] recently found delirium to be a risk factor for anxiety 3 months after stroke, our findings suggest that the subsequent anxiety symptoms can be present or even increase over a longer timeframe.…”
Section: Discussioncontrasting
confidence: 80%
“…Their verbal behavior may include cursing, screaming, or hostile muttering. In some cases, these behaviors are one of the broad manifestations of delirium [ 4 ] that include disturbances in attention, awareness, and cognition. Studies have also described a so-called “catastrophic reaction,” [ 5 , 6 ] which is a constellation of symptoms including anxiety reactions, tears, aggressive behavior, refusal, and swearing [ 5 ].…”
Section: Anger As a Results Of Strokementioning
confidence: 99%
“…Moreover, these behaviors generally subside over time along with the disappearance of other delirious or aphasic symptoms. 4,5 Thus, the aggressive behaviors shown in these patients are unlikely to be an anger based on true emotion disturbances.…”
Section: Phenomenology and Terminologymentioning
confidence: 90%
“…48 The pooled prevalence of post-stroke depression was estimated at approximately 30%, but the results from single studies have varied from 5% to 84%. [49][50][51] Depression occurs most frequently over a short period following the acute phase of stroke, and the percentage of remission is significant. However, high rates of recurrence and new cases are observed, even after a long period following a stroke.…”
Section: Association With Depressionmentioning
confidence: 99%